Comparison between cement paste and asphalt mastic modified by carbonaceous materials: Electrical and thermal properties. (20th July 2019) - Arabzadeh, Ali; Sassani, Alireza; Ceylan, Halil; Kim, Sunghwan; Gopalakrishnan, Kasthurirangan; Taylor, Peter C.
Highlights: Optimum carbon fiber content of paste is smaller than that of mastic. Compared with paste, resistivity of mastic is more temperature dependent. Heat generation has a reciprocal relationship with resistivity. The lower the resistivity, the higher the heat generation rate. Abstract: Asphalt mastic and cement paste are matrices used to fill voids between aggregates in hot mix asphalt and Portland cement concrete. These matrices, in this study, are modified with carbon fiber (CF) – at variable dosage rates – and graphite powder – at a constant dosage rate – to produce electrically-conductive asphalt mastic and electrically-conductive cement paste for de-icing and anti-icing purposes. The purpose is to study the electrical behavior of conductive mastic and conductive paste in analogous conductive material contents, then demonstrate their heating efficiency under identical energy conditions, a novel feature of this study. Optimum CF contents are identified and temperature-related volume resistivity variation are studied at certain CF contents, another novel feature of this study. Heat generation efficiency is analyzed using infrared thermography (IRT) at a few different CF content values equal to or greater than the optimum. According to the findings of this study, conductive paste with higher conductivity exhibits stable electrical behavior when exposed to a temperature change, while conductive mastic's volume resistivity drops as temperature decreases. Also, this study shows that both conductive mastic and conductive paste are capable of generating a satisfactory level of heat if modified with proper dosage rates of conductive materials.